Nailbiter. Volume 1, There will be blood - Williamson, Joshua; Williamson, Joshua; Henderson, Mike, 1981- (Image Comics, 2014)
"Where do serial killers come from?" and why has Buckaroo, Oregon given birth to sixteen of the most vile serial killers in the world? NSA Agent Nicholas Finch needs to solve that mystery in order to save his friend, and he'll have to team up with the infamous Edward "Nailbiter" Warren to do it.